2021
DOI: 10.31219/osf.io/gu5aq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peran Pengawas dalam Meningkatkan Mutu Madrasah Aliyah di Surabaya

Abstract: Pengawas madrasah memiliki peran penting dalam meningkatan mutu madrasah. Pengawas berperan melakukan supervisi akademik dan supervisi manajerial. Pengawas madrasah mempunyai tugas melaksanakan supervisi akademik dan manajerial pada madrasah. Pengawas berkewajiban membantu meningkatkan profesionalisme guru untuk meningkatkan mutu proses pembelajaran. Pengawas juga berkewajiban membantu kepala madrasah untuk meningkatkan mutu madrasah

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…School personnel consider that the majority of educational supervisors are not appointed based on academic qualifications or professionalism, but rather are influenced by factors such as the expiration of the structural term of office, transfers due to errors in the original work unit, selection as an alternative to extending the retirement age, and the view that work as a supervisor lighter because of the relatively loose reins. In addition, the assumption that most supervisors are senior civil servants may make it difficult for others to provide criticism, creating an atmosphere that appears reluctant (Sofanudin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…School personnel consider that the majority of educational supervisors are not appointed based on academic qualifications or professionalism, but rather are influenced by factors such as the expiration of the structural term of office, transfers due to errors in the original work unit, selection as an alternative to extending the retirement age, and the view that work as a supervisor lighter because of the relatively loose reins. In addition, the assumption that most supervisors are senior civil servants may make it difficult for others to provide criticism, creating an atmosphere that appears reluctant (Sofanudin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Supervisory development in improving teacher performance in the learning process, fostering the preparation of annual program documents and learning implementation plans (RPP), fostering teachers who have additional assignments, and the assessment results are reported to the teacher being assessed. Recommendation (Posangi, 2021), The Role of Madrasa Supervisors in Improving Madrasah Teacher Professionalism, results in The role of school supervisors is to maintain and guide teachers to remain professional, including academic Supervision and managerial Supervision (Susilaningsih, 2018) from title Supervisory Management in Improving the Professionalism of Islamic Religious Education Teacher Performance. From this research, it can be concluded that several actions must be taken by a supervisor to improve the performance of PAI teachers, namely by preparing good program planning, implementing the program that has been planned with an academic survey conducted by the supervisor , assessing and evaluating work programs carried out by PAI teachers and following up and solving problems (Isyaroh, 2023).…”
Section: Introductionmentioning
confidence: 99%